2009
DOI: 10.1080/09637480902873781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cake made from whole soy powder on postprandial blood glucose and insulin levels in human subjects

Abstract: We investigated the glycemic index (GI) and the insulinemic index (II) of cake made from whole soy powder (SBC) and the suppressive effects of SBC on the postprandial blood glucose and insulin by other carbohydrate foods. Furthermore, breath hydrogen excretion was simultaneously investigated. Twenty subjects were given 114 g SBC, 144 g cooked paddy-rice, and 60 g SBC with 144 g cooked paddy-rice in random order using a within-subject, repeated-measures design. Blood and end-expiratory gas were collected at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…A similar finding was made in a study that tested the effect of soy nuts or soy protein isolate on blood glucose response in postmenopausal women with MetS [97]. In persons with T2D, blood glucose and insulin responses were lowered in those consuming a nutrition bar made from soybeans compared to an isocaloric cookie control [98], and whole soy powder significantly reduced the glucose, but not insulin, response compared to white rice [99]. …”
Section: Interventional Studies Involving Soysupporting
confidence: 63%
“…A similar finding was made in a study that tested the effect of soy nuts or soy protein isolate on blood glucose response in postmenopausal women with MetS [97]. In persons with T2D, blood glucose and insulin responses were lowered in those consuming a nutrition bar made from soybeans compared to an isocaloric cookie control [98], and whole soy powder significantly reduced the glucose, but not insulin, response compared to white rice [99]. …”
Section: Interventional Studies Involving Soysupporting
confidence: 63%
“…This study was designed as a singleblinded, placebo-controlled study, and was carried out as described in our previous study [8,29,30], under the direction of a medical doctor.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…In addition, these supplements have low glycemic index (GI) values. It has been reported that soy-based foods are eŠective in suppressing increases in blood glucose (Ercan et al, 1994;Iwashita et al, 2008;Oku et al, 2009) and have a``second-meal eŠect'' that suppresses increases in blood glucose from the subsequent meal (Iwashita et al, 2008;Liljeberg and Bjorck, 2000). These eŠects suggest that soy-based foods might be eŠective tools for weight loss and blood glucose control in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%